The gap between consumer and retailer for GSK’s one of the growing oral healthcare brand “Sensodyne” in Bangladesh - Mahin, Md Rifath Alam (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.